ALTERNATIVE SOURCES OF FINANCING ENTREPRENEURIAL UNDERTAKINGS IN AGRICULTURE - Njegomir, Vladimir; Tepavac, Rajko; Ivanišević, Nenad (Economics of Agriculture, 2017)
Insuffciency of internal fnancial resources and limited access to external sources of capital, as one of the key problems, local agricultural producers - entrepreneurs usually describe with high cost of capital, complicated procedures, lack of transparency in regard to the settlement of credit requests and problems with security of loans. The aim of this study is to analyze the possibilities of facilitating access to increased volume of capital for domestic entrepreneurs in agriculture by using funding sources that are applied in developed economies for fnancing entrepreneurs. In order to achieve the stated aim, the subject of investigation in this paper is the analysis of alternative sources of fnancing, which use or increased adoption in Serbia would provide greater availability of capital for agricultural producers and others across the chain of agrobusiness complex and thus the promotion of entrepreneurrial activity, and consequently, greater competitiveness and greater Income of domestic agricultural producers and others across the chain of agrbusiness indirectly leading to increased economic growth and improvement of the welfare.